STDP and mental retardation: dysregulation of dendritic excitability in Fragile X syndrome - Meredith, Rhiannon M.; Mansvelder, Huibert D. (Frontiers in Synaptic Neuroscience, 2010)
Development of cognitive function requires the formation and refinement of synaptic networks of neurons in the brain. Morphological abnormalities of synaptic spines occur throughout the brain in a wide variety of syndromic and non-syndromic disorders of mental retardation (MR). In both neurons from human post-mortem tissue and mouse models of retardation, the changes observed in synaptic spine and dendritic morphology can be subtle, in the range of 10-20% alterations for spine protrusion length and density. Functionally, synapses in hippocampus and cortex show deficits in long-term potentiation (LTP) and long-term depression (LTD) in an array of neurodevelopmental disorders including Down’s, Angelman, Fragile X and Rett syndrome. Recent studies have shown that in principle the machinery for synaptic plasticity is in place in these synapses, but that significant alterations in spike-timing-dependent plasticity (STDP) induction rules exist in cortical synaptic pathways of Fragile X MR syndrome. In this model, the threshold for inducing timing-dependent long-term potentiation (tLTP) is increased in these synapses. Increased postsynaptic activity can overcome this threshold and induce normal levels of tLTP. In this review, we bring together recent studies investigating STDP in neurodevelopmental learning disorders using Fragile X syndrome as a model and we argue that alterations in dendritic excitability underlie deficits seen in STDP. Known and candidate dendritic mechanisms that may underlie the plasticity deficits are discussed. Studying STDP in monogenic MR syndromes with clear deficits in information processing at the cognitive level also provides the field with an opportunity to make direct links between cognition and processing rules at the synapse during development.